Guinea Pig Manure and Mineral Fertilizers Enhance the Yield and Nutritional Quality of the INIA 619 Maize Variety on the Peruvian Coast - Calero Rios, Emilee Nahomi (2025)
Sustainable fertilization using local resources like manure is crucial for soil health. This study evaluated the potential of guinea pig manure to replace mineral fertilizers in hard yellow maize (hybrid INIA 619) under Peruvian coastal conditions. A split-plot design tested four doses of guinea pig manure (0, 2, 5, 10 t ha-1) and four levels of mineral fertilization (0%, 50%, 75%, 100%). The study assessed plant height, ear characteristics, yield, and nutritional quality parameters. The results indicated that 100% mineral fertilization led to the highest plant height (229.67 cm) and grain weight (141.8 g). Yields of 9.19 and 9.08 t ha-1 were achieved with 5 and 10 t ha-1 of manure, while 50% mineral fertilization gave 8.8 t ha-1, similar to the full dose (8.7 t ha-1). Protein content was highest with 10 t ha-1 of manure combined with mineral fertilization. However, no significant differences were found between the 50%, 75%, and 100% mineral fertilizer doses. In conclusion, applying guinea pig manure improved nutrient use efficiency, yield, and grain protein quality in maize, reducing the need for mineral fertilizers by up to 50%. This provides a sustainable fertilization strategy for agricultural systems.